Neural signal variability relates to maladaptive rumination in depression. (December 2022) - Philippi, Carissa L.; Leutzinger, Katie; Pessin, Sally; Cassani, Alexis; Mikel, Olivia; Walsh, Erin C.; Hoks, Roxanne M.; Birn, Rasmus M.; Abercrombie, Heather C.
Abstract: Rumination is a common feature of depression and predicts the onset and maintenance of depressive episodes. Maladaptive and adaptive subtypes of rumination contribute to distinct outcomes, with brooding worsening negative mood and reflection related to fewer depression symptoms in healthy populations. Neuroimaging studies have implicated several cortical midline and lateral prefrontal brain regions in rumination. Recent research indicates that blood oxygen level-dependent (BOLD) signal variability may be a novel predictor of cognitive flexibility. However, no prior studies have investigated whether brooding and reflection are associated with distinct patterns of BOLD signal variability in depression. We collected resting-state fMRI data for 79 women with different depression histories: no history, past history, and current depression. We examined differences in BOLD signal variability (BOLDSD ) related to rumination subtypes for the following regions of interest previously implicated in rumination: amygdala, medial prefrontal, anterior cingulate, posterior cingulate, and dorsolateral prefrontal cortices (dlPFC). Rumination subtype was associated with BOLDSD in the dlPFC, with greater levels of brooding associated with lower BOLDSD in the dlPFC, even after controlling for depression severity. Depression history was related to BOLDSD in the dlPFC, with reduced BOLDSD in those with current depression versus no history of depression. These findings provide a novel demonstration of the neural circuitry associated with maladaptive rumination in depression and implicate decreased prefrontal neural signal variability in the pathophysiology of depression. Highlights: We examined the link between rumination subtypes and BOLDSD in depression. Greater brooding was correlated with depression symptom severity. Lower variability in dlPFC was related to brooding after controlling for depression. Variability in dlPFC was lower in current depression versus no depression groups. Findings suggest BOLD signal variability may be an important marker of rumination.